Ethnographies of uncertainty in Africa - Cooper, Elizabeth, 1976-; Pratten, David (Houndmills, Basingstoke, Hampshire : Palgrave Macmillan, 2015)
"This collection explores the productive potential of uncertainty fo r people living in Africa as well as for scholars of Africa. The releva nce of the focus on uncertainty in Africa is not only that contemporary life is objectively risky and unpredictable (since it is so everywhere and in every period), but that uncertainty has become a dominant trope in the subjective experience of life in contemporary African societies . The contributors investigate how uncertainty animates people's ways o f knowing and being across the continent. An introduction and eight eth nographic studies examine uncertainty as a social resource that can be used to negotiate insecurity, conduct and create relationships, and act as a source for imagining the future. These in-depth accounts demonstr ate that uncertainty does not exist as an autonomous, external conditio n. Rather, uncertainty is entwined with social relations and shapes peo ple's relationship between the present and the future. By foregrounding uncertainty, this volume advances our understandings of the contingenc y of practice, both socially and temporally"--
Includes bibliographical references and index.
Keywords: Pragmatism -- Social aspects -- Africa; Forecasting -- Social aspects -- Africa; Social problems -- Addresses, essays, lectures; Ethnology -- Africa; Africa -- Social conditions -- 1960-